AKTİF SPOR YAPAN BİREYLERDE ZAMAN YÖNETİMİ: DEMOGRAFİK FARKLILIKLAR (ELAZIĞ İLİ ÖRNEĞİ) - YURDAGÜL, SİNAN (Fırat Üniveristesi, 2016)
Zaman, herkesin elde ettiği, lakin aynı ölçüde kullanamadığı son derece önemli ve eşsiz bir kaynaktır. Zaman yönetimi; üreticiliği arttırmak için, belirli aktiviteler üzerinde harcanan zamanı düzenli ve planlı bir şekilde kontrol etme yöntemini amaç edinmektedir. Çalışmanın amacı, aktif spor yapan bireylerin zamanını planlamada, kullanmada ve değerlendirmede davranışlarını incelemektir. Araştırmanın evrenini Elazığ ilinde aktif spor yapan bireyler oluştururken, örneklemini ise tesadüfi olarak seçilmiş 680 sporcu oluşturmaktadır. Anketten elde edilen veriler frekans, yüzde, aritmetik ortalama, ikili gruplar için t testi, çoklu gruplar için tek yönlü varyans analizi (Anova) uygulanarak sonuçlar tablolar halinde gösterilmiştir. Sonuç olarak aktif spor yapan bireylerin boş zaman yönetiminde, üniversite mezunlarının spor yapma yılı 6-10 yıl olan sporcular zamanı değerlendirmede daha etkin olduğunun görüldüğü ve Spora başlamada en önemli faktörün Akraba ve Arkadaşları olduğu ve bu faktörün boş zamanı değerlendirmede sporcu üzerindeki etkisinin daha fazla olduğu görülmüştür. Medeni durum değişkenindeki evli bireylerin 26-30 ve 31-35 yaş arasındaki sporcuların zaman yönetiminde daha özenli oldukları tespit edilmiştir. Anahtar Kelimeler: Sporcu, zaman, zaman yönetimi, zaman planlanması, zaman tutumu

Time is a unique and extremely important resource that everyone has equally but not can be used in the same way. Time management aims to control process the time, which spent on spesific activities, in a conscious way. The aim of this study is to analyse behaviours of active sportive individuals when they planning, using and valuing (spending efficiently) their time. Active sportive individuals in Elazig are at the basis of universe of this research and the 680 people for the investigation who were chosen at random are at the basis of sample of this research. Final results are shown as tables which obtained datas in petition applied by frequency, percentage, arithmetic average, t test for binary groups, and analysis of variance (ANOVA) for the multi groups. It is determined that,% 54 of people who have master or bachelor degree, % 78,8 of married people, % 78, 9 of people who live in metropoles, %84,2 of people who are between 31-35 age, %73,6 of people who make sports between 6-10 years, make plan daily. Relatives are determined as the most important factor that refer people to make sport with %79,5 percent. As a result, it has been shown that active sportive people who have bachelor degree are more efficient in free time management. Relatives and friends are the most important factor to refer people to start sport and affect on people much in free time planning. Also it has been shown that married people in marital status variable, 26-30 and 31-35 aged sportsmen are more carefull. Key Words: Sportsman, time, time management, time planning, sports attitude
Time management fort he individuals who actively do sports demographic differences ( Elazig province example)
Keywords: Spor